The Anatomy of the Global Saving Glut - Luis Bauluz; Filip Novokmet; Moritz Schularick (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper provides a household-level perspective on the rise of global saving and wealth since the 1980s. We calculate asset-specific saving flows and capital gains across the wealth distribution for the G3 economies – the U.S., Europe, and China. In the past four decades, global saving inequality has risen sharply. The share of household saving flows coming from the richest 10% of household increased by 60% while saving of middle-class households has fallen sharply. The most important source for the surge in top-10% saving was the secular rise of global corporate saving whose ultimate owners the rich households are. Housing capital gains have supported wealth growth for middle-class households despite falling saving and rising debt. Without meaningful capital gains in risky assets, the wealth share of the bottom half of the population declined substantially in most G3 economies.
Keywords: D31; E21; E44; N32; 330; income and wealth inequality; household portfolios; historical micro data